The Characteristics of Nugget Fortified Calcium From Chicken Eggshell Powder - Made Gde Wisnu Merta; Ni Made Wartini; I Made Sugitha (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Nugget is favorite fast food, which contain a high cholesterol and low in minerals such as calcium. Chicken eggshell is an idle resource, which contain high calcium. Fortification of calcium sources from chicken eggshell powder is a good innovation to increase the nutritional value of nuggets, and utilizing of idle resources that are currently not properly managed. The purpose of this research was to determine the effect of additional chicken eggshells powder as calcium fortification to the characteristics of nuggets, and percentage of additional chicken eggshell powder to produce the best nuggets. This research was an experimental study using a Completely Randomized Design with the treatment of additional chicken eggshell powder for nuggets. The treatment carried out with five levels of 0%, 5%, 10%, 15%, and 20%, by weight of the nugget raw material. Each treatment was repeated three times. The results of physical, chemical, and organoleptic characteristics analysis showed that the additional of chicken eggshell powder has a significant effected to the water content, ash content, protein content, calcium content, taste, and texture, but did not significant affected the fat content, pH value, hardness level, color, and flavor of the nuggets. Based on the results of the effectiveness test, the best treatment in this research was the addition of 5% chicken eggshell powder. The addition of chicken eggshell powder can significantly increase calcium and ash content of the nuggets, but significantly decrease taste and texture of the nuggets. The addition of 5% chicken eggshell powder produced the best nuggets.